Effects of Live Yeast and Yeast Extracts with and without Pharmacological Levels of Zinc on Nursery Pig Growth Performance and Fecal Consistency - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; Hilda I. Calderón; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joseph A. Loughmiller (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 360 weanling barrows (Line 200 × 400, DNA Genetics; initial BW 12.4 ± 0.05 lb) were used in a 42-d study to evaluate yeast-based pre- and probiotics (Phileo by Lesaffre, Milwaukee, WI) in diets with or without pharmacological levels of Zn on growth performance and fecal dry matter (DM). Pens were assigned to 1 of 4 dietary treatments with 5 pigs per pen and 18 pens per treatment. Dietary treatments were arranged in a 2 × 2 factorial with main effects of live yeast-based pre- and probiotics (none vs. 0.10% ActiSaf Sc 47 HR+, 0.05% SafMannan, and 0.05% NucleoSaf from d 0 to 7, then concentrations were lowered by 50% from day 7 to 21) and pharmacological levels of Zn (110 vs. 3,000 ppm from d 0 to 7, and 2,000 ppm from d 7 to 21 provided by ZnO). All pigs were fed a common diet from d 21 to 42 post-weaning. There were no yeast × Zn interactions or effects due to yeast additives observed on any response criteria. From d 0 to 21 and d 0 to 42, pigs fed pharmacological levels of Zn had increased (P<0.001) ADG and ADFI. Fecal samples were collected on d 4, 21, and 42 from the same three pigs per pen for DM analysis. On d 4, pigs fed pharmacological levels of Zn had greater fecal DM (P= 0.043); however, no differences were observed on d 21 or 42. In conclusion, pharmacological levels of Zn increased ADG, ADFI, and d 4 post-weaning fecal DM. There was no response observed from live yeast and yeast extracts for any growth or fecal DM criteria.
Keywords: anti-microbial resistance; nursery pigs; probiotics; yeast; yeast extracts; zinc